(untitled) (Research, Society and Development, 2021)
The present work aims to identify the frequency of training of the nursing staff of a pediatric oncology unit and the articulation of the knowledge acquired with the assistance provided. In order to achieve the proposed objective and having the cross-sectional study as a methodological approach, of a descriptive nature and quantitative approach. The research was carried out in a reference hospital in Sergipe, where 63 professionals from the nursing team were approached. The collection was carried out individually between the months of March and April 2017. The collected data were organized in a database and analyzed using the data analysis technique. The results showed a deficiency in training in the area of pediatric oncology, more than half of the professionals did not obtain any type of knowledge focused on this theme in their training process, in addition to the low supply of training by the current sector with a frequency of only 12.7% and little demand from professionals, even with a conception of the benefits of training. Finally, there was a deficit in the frequency of training, directed to pediatric oncology, from training to professional practice, presenting itself as a major obstacle to qualified assistance.